The South Africa government invests in water resources, irrigation and infrastructure improvements and adopts policies for climate change resilience, supported by CGIAR and partners’ research - CGIAR Research Program on Water, Land and Ecosystems (2021)
Since 2013, the Government of South Africa, WLE/PIM/IFPRI and research partners have collaborated to assess the role of water infrastructure in adapting to potential climate change impacts. This has helped policymakers prioritize building resilience into infrastructure investments and implement climate sensitive development programs. The findings and recommendations of this research have been built into major policy and investment plans, including Operation Vulindlela, highlighted in the President’s 2022 State of the Nation Address as one of five key sectors.